Studying the impact of rules of origin on foreign trade in Syria (Latakia University Journal - Economic and Legal Sciences Series, 2023)
The study aimed to show the impact of the rules of origin on foreign trade in Syria, in an effort to identify the extent to which the rules of origin benefit the Syrian economy, or otherwise hinder it. Rules or tools for foreign trade in Syria.The most important results of the study were:The distinctive identification marks of the rules of origin system affect foreign trade in Syria.Control over the traceability system and rules of origin affect foreign trade in Syria.- Storage and access to the rules of origin information affects foreign trade in Syria.